2013
DOI: 10.1155/2013/517478
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Protects against Ischemia/Reperfusion Injury Associated with Reduced Apoptosis in Rat Liver

Abstract: Propofol is an intravenous anesthetic, reported to have a protective effect against ischemia/reperfusion (I/R) injury in heart and brain, but no definite data are available concerning its effect in hepatic I/R. This work investigated the effect of propofol anesthesia on hepatic I/R injury using in vivo rat model. Four groups of rats were included: sham operated, I/R (30 min ischemia and 2 h reperfusion), I/R treated with propofol (10 mg/kg/h), and I/R treated with propofol (20 mg/kg/h). Liver enzyme leakage, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…The TNF-α level in rats that underwent PHT under propofol anesthesia was significantly lower than in those that underwent PHT under ketamine anesthesia, suggesting that propofol might have a protective effect on the liver. These findings are in agreement with those of Abdel-Wahab et al 17 , who reported attenuation of the TNF-α level and expression of apoptotic genes upon propofol infusion in ischemic livers.…”
Section: ■ Discussionsupporting
confidence: 93%
“…The TNF-α level in rats that underwent PHT under propofol anesthesia was significantly lower than in those that underwent PHT under ketamine anesthesia, suggesting that propofol might have a protective effect on the liver. These findings are in agreement with those of Abdel-Wahab et al 17 , who reported attenuation of the TNF-α level and expression of apoptotic genes upon propofol infusion in ischemic livers.…”
Section: ■ Discussionsupporting
confidence: 93%
“…The mRNA expression of Bax, Bcl-2 and Caspase-3 was determined to evaluate whether AFB 1 -induce apoptosis in rat liver is related to the mitochondrial pathway. The increased in mRNA expression of Bax and Caspase-3 and the decreased in mRNA expression of Bcl-2 and the ratio of Bcl-2/Bax in hepatocytes of rats treated with AFB 1 suggest that the excessive apoptosis of hepatocytes induced by AFB 1 was onset by the mitochondrial signaling pathway (Abdel-Wahab and Al-Harizy, 2013;Abdel-Aziem et al, 2014). It was demonstrated also that AFB 1 could lead to cellular apoptosis via mitochondrial or cell death receptor pathways (Abdel-Aziem et al, 2011;Peng et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The ischemic liver is characterized by cellular apoptosis and programmed cell death, which is recognized by the caspase family in which caspase-3 is the executive caspase [ 67 ]. Growing evidence suggested that TNF- α and oxidative stress played a crucial role in magnifying the apoptosis in the ischemic liver [ 23 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HIR injury was performed as described in previous studies [ 22 , 23 ]. Rats were anesthetized with a mixture of ip 80 mg/kg ketamine (Ketamax-50, Troikaa Pharmaceuticals Ltd., Gujarat, India) and 10 mg/kg xylazine (Xyla-Ject®, Adwia Co., 10th of Ramadan, Egypt) [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%